Hydrogen peroxide stress stimulates phosphorylation of FoxO1 in rat aortic endothelial cells - Wang Ye-yu; Chen Si-min; Li Hao (Acta Pharmacologica Sinica, 2016)
Aim: To examine whether the phosphorylation of the O subfamily of forkhead transcription factors (FoxO) is involved in response to oxidative stress in rat aortic endothelial cells (RAECs). Methods: RAECs were treated with H2O2 and phosphorylation status of proteins were evaluated by Western blot analysis. The subcellular localization of FoxO1 was determined by nuclear and cytosolic fractionation followed by Western blot analysis as well as immunocytochemistry. The transcriptional activity of FoxO1 in H2O2stress was assessed by luciferase reporter assay. Expression of FoxO1 target gene was determined by real-time PCR analysis. Results: H2O2 stress stimulated phosphorylation of FoxO1 at Thr24 and Ser256 in a concentration and time dependent manner in RAECs. Pretreatment of RAECs with PI-3K inhibitors abolished the activation of Akt and prevented the phosphorylation of FoxO1. Aktmediated phosphorylation promoted nuclear exclusion of FoxO1. An IRS-driven luciferase activity transactivated by exogenous FoxO1 was modestly suppressed by hydrogen peroxide stress. The expression of Bim, a target gene of FoxO factors, was negatively regulated by Akt-mediated phosphorylation in response to hydrogen peroxide stimulation. Conclusion: Our data demonstrate that phosphorylation of FoxO1 by PI-3K/Akt signaling is implicated in response to oxidative stress in vascular endothelial cells.